Studi Pembuatan Mie Kering Berbahan Baku Tepung Singkong Dan Mocal (Modified Cassava Flour) - Neny Mariyani (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2011)
The objectives of this research is to find the best formulation of cassava flour and mocal (modified cassava flour) based dry noodle which can compete with wheat flour based dry noodle. This research consist of experiments with several variation of composition cassava flour and mocal including 40% and 50%.  Mocal used in this research was produced from spontaneous fermentation which would be compared with commercial mocal which was usually produced from non-spontaneous fermentation. Spontaneous fermentation is natural fermentation process which no added  microorganisms.  The sensory evaluation of dry and rehydration noodles which are physical appearance, color, odor, taste, gumminess and extensibility. The data was analized by ANOVA (Analysis of Variance) and then Duncan Test. The best result was then examined`for it’s chemical composition like moisture content, ash, crude fat, protein and carbohydrate (crude fiber). The result showed that the best formulation to produced dry noodle use mocal from spontaneous fermentation with composition 40% mocal and 60% wheat flour. The best dry noodle contained (wet weight basis) of 12,31% moisture content, 3,97% ash, 6,69% protein, 1,13% crude fat and 3,86% crude fiber.Keyword : cassava flour, mocal, spontaneous fermentation, commercial mocal